Strategi Pengelolaan Wakaf Uang Dalam Mengembangkan Eduwisata Halal (Studi Masjid Ki Marogan Palembang) - Ahmad Martinus Aldaris; Fakhrina; Oki Sapitri Menghayati (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
In the economic system, waqf plays a role as a means of increasing productive assets for the management of a society. This waqf is the most important part of the development of Muslim civilization, especially the tourist attraction at the KI Marogan Mosque in Palembang. Based on the type, waqf is divided into two types, namely immovable and movable waqf. In general, people only know about the implementation of waqf in immovable forms such as land, even though in practice, waqf can be paid in the form of property, one of which is cash waqf. With this, researchers are interested in conducting research on Cash Waqf Management Strategies in Developing Halal Edutourism, studying the KI Maroan Mosque Palembang. The research method used by researchers in this research is a qualitative method with a descriptive approach, while data collection is carried out through survey, interview and documentation techniques. And the data sources obtained from research subjects are primary data and secondary data. Based on the results of research conducted, it is known that cash waqf is still not widely known and understood by the general public, especially regarding understanding and awareness of cash waqf. This phenomenon is caused by two main factors, namely intenal and external factors. And also the management strategy is still not working well because there is poor communication between the old and new order management, resulting in a lack of effective information obtained by the public and tourists who visit the KI Marogan Mosque in Palembang. Therefore, there are several ways to overcome this by managing cash waqf funds more transparently so as not to cause negative thoughts and also providing education to the public and tourists about the importance of cash waqf.